PENGARUH PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI PADA WARUNG MAKAN BU YATI SOLO - Sumaryanto, Nanang Qosim (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
This research is aimed to analysis the signification effect of the product toward costumer satisfaction; the effect of price toward costumer satisfaction; the effect of product toward buying decision; the effect of price toward buying decision; the effect of customer satisfaction toward buying decision; the effect of product toward buying decision which mediated by customer satisfaction; the effect of price toward buying decision which mediated by customer satisfaction. The population of this research are all customer of Bu Yati Solo’s food stall. Sample is taken from 100 respondent by Incidental sampling technic. Colection data technic use quesionnaire and observation trough test of validation and previous reliability. Test of condition of regretion use test of classic assumption. The analyzing data technic use line analysis. The result of this research shows that the product gives significant effect toward customer satisfaction; the price gives significant effect toward customer satisfaction; the product gives significant effect toward buying decision; the price does not give significant effect toward buying decision; the customer satisfaction gives significant effect toward buying decision; the customer satisfaction does not mediate the product effect toward buying decision; the customer satisfaction does not mediate the price effect toward buying decision. Keywords: product and price, cutomer satisfaction, buying decision.